ANALYSIS OF THE EFFECTIVENESS OF THE POLICY IMPLEMENTATION PROGRAM FOR HANDLING INFRASTRUCTURE AND PUBLIC FACILITIES (PPSU) OF CLEANING SERVICES IN GONDANGDIA VILLAGE IN 2019 - Tuswoyo Tuswoyo; Ahmad Buchari Nurachman (International Peneliti Ekonomi, Sosial dan Teknologi, 2020)
Lack of public awareness in maintaining environmental cleanliness which is increasing every day along with the increase in population will have an impact on the environment and society. Handling of cleanliness that includes sanitation facilities, infrastructure, channels, and infrastructure of parks is one of the solutions that the DKI Jakarta Provincial Government minimizes problems in the Capital City of Jakarta. DKI Jakarta Governor Basuki Tjahya Purnama issued the Governor Regulation Number 7 of 2017 concerning Handling of Urban Village Public Infrastructure and Facilities (PPSU) as a means for the DKI Jakarta Provincial Government to respond and provide services for handling city sanitation to the community. The method used in this research is descriptive qualitative with data collection technique conducted through observation, documentation, and in-depth interviews with informants with questions according to the analysis of the effectiveness of the PPSU policy implementation at the urban village level. The purpose of this study describes the extent to which the effectiveness of the policies set by the Provincial Government of DKI Jakarta in providing city cleanliness handling services by orange troops who are included in the PPSU officers. Based on the results of research conducted by a researcher, DKI Jakarta Province made efforts to accelerate the functioning of public infrastructure and facilities. Where this PPSU was a work that needed to be immediately implemented and could not be delayed because it might result in loss, hazard, and interfered the Public/Community interest; the Policy was implemented at the urban village level because it was a basic level service that interacted directly with the community.